Urban Futures: Utopia and the alchemy of science fiction - Lim , CJ (Architecture Image Studies, 2021)
The paper examines if our raison d’être stood to interrogate the world of the built environment through a rich alchemy of science fiction, might our urban futures take alternative forms to build a fundamentally different idea of society? Science fiction and utopia are about the ‘other’ and occupy an indeterminate state beyond our consciousness. The guiding light and dare of uncertainty are crammed with spatially suggestive concepts and intensity that in provoking political commentary, also ignites our imagination. Its speculative nature consistently presents the world anew with re-invigorated critical faculties, and perhaps a greater perception of the incongruity of our society, cities and infra structures in the age of pandemic, protests and politics. The perfect world, in the case studies, is far more imperfect than is at first seemed, where the understanding and sympathies for existing traditions of protection, provision and participation are turned upside-down.